2019
DOI: 10.1111/ajco.13157
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of enhancement rate by enhanced ultrasound in hepatitis B virus‐positive hepatocellular carcinoma undergoing radiofrequency ablation

Abstract: Aim:To assess the prognostic significance of enhancement rate (ER) measured by contrastenhanced ultrasonography (CEUS) in patients with hepatocellular carcinoma (HCC) undergoing radiofrequency ablation (RFA). Materials and methods:A total of 253 patients with single primary HCC undergoing preoperative CEUS and RFA were enrolled in this study. The ER were evaluated though pretreatment CEUS.After a mean follow-up of 36.8 ± 10.2 months, the correlation of ER measured by CEUS and survival after RFA was analyzed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…In a prospective study, Maruyama et al (44) showed that HCC lesions with early arterial phase intensity difference less than 10 dB had a significantly higher rate of recurrence after radiofrequency ablation than those with intensity difference greater than 10 dB. However, Zhou et al (45) recently showed that lesions with higher pretreatment enhancement rate in terms of decibels per second had lower overall survival and recurrencefree survival than those with lower enhancement rate. Although there is an overall paucity of data on pretreatment lesion enhancement characteristics for predicting response to liver-directed therapy, future increased clinical use of CEUS for pretreatment evaluation of liver lesions could provide the necessary data to answer these questions.…”
Section: Predicting Response Before Liver-directed Therapiesmentioning
confidence: 99%
“…In a prospective study, Maruyama et al (44) showed that HCC lesions with early arterial phase intensity difference less than 10 dB had a significantly higher rate of recurrence after radiofrequency ablation than those with intensity difference greater than 10 dB. However, Zhou et al (45) recently showed that lesions with higher pretreatment enhancement rate in terms of decibels per second had lower overall survival and recurrencefree survival than those with lower enhancement rate. Although there is an overall paucity of data on pretreatment lesion enhancement characteristics for predicting response to liver-directed therapy, future increased clinical use of CEUS for pretreatment evaluation of liver lesions could provide the necessary data to answer these questions.…”
Section: Predicting Response Before Liver-directed Therapiesmentioning
confidence: 99%
“…The mechanisms of malignant behaviors from recurrent HCC after RFA have been increasingly reported (22). Early detection and diagnosis of local recurrence in HCC patients' follow-up have become important issues (5,9,(23)(24)(25)(26). A previous study (27) indicated that isoenhancement in all vascular phase patterns on CEUS was found in >50% of recurrent lesions, indicating a high risk of HCC.…”
Section: Discussionmentioning
confidence: 99%